Increase in nuclear cell‐free DNA is associated with major adverse events in adult and pediatric heart transplant recipients. Issue 1 (24th November 2021) - Zangwill, Steven D.; Deshpande, Shriprasad R.; Simpson, Pippa M.; Liang, Huan Ling; Zhang, Liyun; Dasgupta, Mahua; Richmond, Marc E.; Kindel, Steven J.; Bichell, David P.; Mahle, William T.; Wigger, Mark A.; Schroder, Jacob N.; et al.
Abstract: Background: Cell‐free DNA is an emerging biomarker. While donor fraction may detect graft events in heart transplant recipients, the prognostic value of total nuclear cell‐free DNA (ncfDNA) itself is largely unexplored. Objective: Explore the relationship between ncfDNA and clinical events in heart transplant recipients. Methods: We conducted a multi‐center prospective study to investigate the value of cell‐free DNA in non‐invasive monitoring following heart transplantation. Over 4000 blood samples were collected from 388 heart transplant patients. Total ncfDNA and donor fraction were quantified. Generalized linear models with maximum likelihood estimation for repeated measures with subjects as clusters were used to explore the relationship of ncfDNA and major adverse events. Receiver operating characteristic curves were used to help choose cutpoints. Results: A ncfDNA threshold (50 ng/ml) was identified that was associated with increased risk of major adverse events. NcfDNA was elevated in patients who suffered cardiac arrest, required mechanical circulatory support or died post heart transplantation as well as in patients undergoing treatment for infection. Conclusions: Elevated ncfDNA correlates with risk for major adverse events in adult and pediatric heart transplant recipients and may indicate a need for enhanced surveillance after transplant.